Rhythmic gymnastics and dyslexia - Senatore, B.; Valentini, M.; Federici, A.; Morsanuto, S.; D'Elia, F. (Journal of Human Sport & Exercise, 2019)
Rhythmic gymnastics is an Olympic sport with enabling and coordinating features characterized by "small tools" such as rope, hoop, ball, clubs and ribbon. The competitive program sees both individual and team performance. Dyslexia is a learning disorder, the failure of the development of hemispheric dominance or conflicts of dominance between the two hemispheres. In addition to having learning problems, people suffering from dyslexia also have problems in cognition of their bodies within space and with the musical rhythm. The aim is to verify if a dyslexic athlete can succeed in practicing this sport competitively, finding benefits in terms of performance, but especially in the sphere of self-esteem and sociality. Through the case study and ethnographic approach it was found that the gymnast manages to achieve the same results as the other gymnasts who train with her, but showing a small difficulty in teamwork. Moreover, after several steps it was found that the gymnast, already having innate physical qualities, during the competitions will be more valid than his training companions, despite his learning difficulties. These results encourage to deepen the links between physical activity and personal aspects because he is an athlete to all intents and purposes, with potential and weaknesses on a par with other athletes.